Chronologies, vegetation, and physical/geochemical data from peat cores, Nejanilini Lake region, Manitoba, Canada, 2008-2009 - Philip Camill (Arctic Data Center, 2016)
Small peat-forming ecosystems in arctic landscapes may play a significant role in the regional biogeochemistry of high-latitude systems, yet they are understudied compared to arctic uplands and other major peat-forming regions of the North. We present a new data set of 25 radiocarbon-dated permafrost peat cores sampled around eight low arctic lake sites in northern Manitoba (Canada) to examine the timing of peat initiation and controls on peat accumulation throughout the Holocene. We used macrofossils and charcoal to characterize changes in the plant community and fire, and we explored potential impacts of these local factors, as well as regional climatic change, on rates of carbon (C) accumulation and C stocks. Peat initiation was variable across and within sites, suggesting the influence of local topography, but 56% of the cores initiated after 3000 B.P. Most cores initiated and remained as drier bog hummock communities, with few vegetation transitions in this landscape. C accumulation was relatively slow and did not appear to be correlated with Holocene-scale climatic variability, but C stocks in this landscape were substantial (mean = 45.4 kg C per square meter), potentially accounting for 13.2 Pg C in the Taiga Shield ecozone. To the extent that small peat-forming systems are underrepresented in peatland mapping, soil organic carbon (SOC) stocks may be underestimated in arctic regions. Mean fire severity appeared to be negatively correlated with C accumulation rates. Initiation and accumulation of soil C may respond to both regional and local factors, and substantial lowland soil C stocks have the potential for biogeochemical impacts on adjacent aquatic ecosystems. More information can be found at doi.org/10.1002/2016JG003662